The Use of Antidiabetic Herbal Remedies by Jordanian Herbalist: A Comparison of Folkloric Practice vs. Evidence-Based Pharmacology - ISSA, REEM; Khattabi, Areen; Alkarem, Tabarak; Altameemi, Omar (Jordan Journal of Pharmaceutical Sciences, 2019)
Traditionally used herbal remedies are an essential part of the Jordanian folklore, due to its abundance in vast sources of ethnomedicine. This study conducted a face to face interview with a random sample of local herbalists, focused on traditionally used antidiabetic herbal remedies. Subsequently, these remedies were validated for evidence-based pharmacological studies, using data in the literature to find out the available information about different clinical, in vitro or in vivo studies. Two traditionally used antidiabetic herbal mixtures were found commonly prescribed, composed of twelve different plant species. Nine species proved to be effective in in vitro, in vivo and clinical evaluations for their antidiabetic effect. Only one species was found to be effective on animal models or as enzyme inhibitor, but not in any clinical studies. Another two species were found to be ineffective neither in invitro, invivo nor in clinical evaluations. This review will help to strengthen the relation between traditional medicine and evidence-based pharmacology. Also, it will shed the light on the ethnomedicine practices in Jordan, revealing some common errors among herbalist’s practices and uses of antidiabetic herbal remedies. We recommend for these traditionally used plants, to go for extensive chemical investigations as well as clinical trials, in order to find out potential new antidiabetic agents.